CHARACTER BASED ON BONA PASOGIT LOCAL WISDOM - Pardomuan Simanullang (Sean Institute, 2022)
Education is a vehicle for the transformation of culture, values, science and technology that has become the center for the development of the nation's character, both through formal and non-formal education. Quality human resources are the main capital to achieve the welfare of the nation. Increasing intellectual, emotional and spiritual intelligence is a prerequisite for the success of Indonesian human development. Education that seeks to produce good citizens is described in nation and character building by instilling the spirit of nationalism in order to form a complete Indonesian human being. This means that education is expected to form students who have national character embodied in the moral values of their citizens, By bringing back the values contained in the many cultures and making them one of the guidelines in the growth of student character, it is believed that they can support superior human resource education. With the creation of superior human resources, superior institutions, superior regions and superior and prosperous nations will be created